Ultrasound measurement of fetal kidney length in the second and third trimester of pregnancy and its correlation with gestational age - Gautam, Mahesh; Khanal, Bipin; Dhakal, Amita; Pathak, Manish Raj; Tiwari, Sagar (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To measure the fetal kidney length in the second and third trimesters of pregnancy and correlate it with the gestational age and other routine fetal parameters.Methods: This prospective cross-sectional study includes 250 pregnant women presented in the Nobel Medical College for ultrasound examination from the period of July 2021 to June 2022. Gestational age was estimated based on the last menstrual date and ultrasonogram. Routine fetal parameters and mean fetal kidney length were measured. The correlation between gestational age, fetal kidney length, and routine fetal parameters was studied.Results: The mean gestational age according to ultrasound and last menstrual period were 35.5 ± 3.4 weeks and 35.2 ± 3.2 weeks respectively. The mean fetal kidney length was 36.8 ± 4.02mm. There was a very strong positive correlation between gestational age and fetal kidney length (r=0.921, p =0.001). Compared to the routine fetal parameters, adding fetal kidney length improved the effectiveness in predicting gestational age. (R2 =0.918 vs. R2 =0.936)Conclusion: Fetal kidney length can be added to the other standard parameters to improve the prediction of gestational age.